Sustainability Performance and Companies Financing: Does Audit Quality Matter? - Muhammad Rafiuddin; Fitri Anisa Nusa Putri; Yuan Chen; Slamet Haryono (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
Public listed companies are increasingly recognizing the importance of corporate social responsibility in their sustainability initiatives. Supporting the stakeholder theory, a commitment for social responsibility activities that reflected by CSR performance as a strategy of firms has created a positive image from stakeholder perceptions. This study examines how corporate social responsibility performance affects companies financing and the role of audit quality. To test the study’s hypotheses, the authors applied linier regressions model on panel data by observing samples of Indonesian Islamic listed companies from 2018 to 2022. The results show that a better CSR performance is associated with lower cost of debt and cost of equity. Moreover, this study also reflect upon the importance of audit quality that proxied by the BIG 4 auditors is found significantly moderates in both cost of debt and cost of equity. Thus, a better corporate social performance with the existence of BIG 4 auditor implies the ability of firms accessing to lower-cost capital by minimized the long term risks. The existence of BIG 4 auditors demonstrated the credibility effective monitoring as a good signals for capital provider or lenders. Our study represents a novelty to enrich the relevant literature on the corporate social responsibility by expanding it towards the role of audit quality on both cost of capital proxies.